Electronic Performance Monitoring in the Digital Workplace: Conceptualization, Review of Effects and Moderators, and Future Research Opportunities - Kalischko, Thomas; Riedl, René (Frontiers in Psychology, 2021)
The rise of digital and interconnected technology within the workplace, including programs that make possible monitoring and surveillance of employees, is unstoppable. COVID-19-induced lockdowns and the resulting increase in home office adoption even increased this trend. Aside from major benefits that may come along with such information and communication technologies (e.g., productivity increase, better resource planning, and increased worker safety), they also enable comprehensive electronic performance monitoring (EPM) which may also have negative effects (e.g., stress increase and job satisfaction reduction). This conceptual article investigates EPM to better understand the development, adoption, and impact of EPM systems in organizations. The EPM literature published since the 1980s constitutes the basis for this conceptual article. We present a framework which is intended to serve as foundation for future studies. Moreover, we reviewed more than three decades of empirical EPM research and identified six major outcomes that are influenced by the use of an EPM system, as well as a large number of moderator variables. Based on our conceptual analyses and the resulting insights, which also include privacy and ethics considerations, we discuss future research opportunities, where we also refer to design implications for EPM systems.